Philippines : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper on the Philippines reviews the diminished volatility of the Republic of Philippines bonds (RoPs), even through a period of extended turbulence cannot be attributed solely to the sanguine global factors currently prevailing across all credit markets. Considerable fiscal gains have already been achieved following the introduction of these reforms. The estimated magnitude of second-round effects for the Philippines is likely an upper bound, as greater competition, ongoing fiscal consolidation, and enhanced monetary policy credibility will likely reduce the scope for second-round effects over time.